We've Been Longing to Fall Apart : a Research of Embodiment, Body and Voice Expression - Mensink, Mathilde, 1991- (2021)
In this paper I will account for and reflect upon my choreographic work “We’ve Been Longing to Fall Apart” as well my creative and embodied working process towards it. The choreography was created as my Individual Project on the third and final year at the BA in Contemporary Dance Practices at Iceland Academy of the Arts. I will describe and discuss my working methods; methods and tools from contemporary dance and other body-practices, as well as my creative approaches and strategies. I aim to contextualize the work within the field of contemporary dance and in relation to the topics it deals with. I work with artistic and creative methods of research. My main methods of production and research are experimentation with/on my own body in movement, synthesis of techniques and ideas as well as self-reflection. I apply my creative, technical and theoretical knowledge of dance- and body- and voice techniques and modalities taught at the Iceland Academy of the Arts and elsewhere. Through this process I have developed towards forming a personal choreographic practice and studio-practice. I have found methods and artistic language to express the topics with which the choreography deals. I have a deepened understanding of how to work with my own performing body and how to utilize my physical, reflective, analytical and creative skills in the research and creation of movement material and choreography.